Lepton Flavor Equilibration and Leptogenesis (2009)
ABSTRACT: We study the role played in leptogenesis by the equilibration of lepton flavors, as could be induced in supersymmetric models by off diagonal soft breaking masses for the scalar lepton doublets ̃mαβ, or more generically by new sources of lepton flavor violation. We show that if ̃mαβ >∼ 1 GeV and leptogenesis occurs below ∼ 100 TeV, dynamical flavor effects are irrelevant and leptogenesis is correctly described by a one-flavor Boltzmann equation. We also discuss spectator effects in low scale leptogenesis by taking into account various chemical equilibrium conditions enforced by the reactions that are in thermal equilibrium. We write down the Boltzmann equation for low scale supersymmetric leptogenesis that includes flavor and spectator effects in the presence of lepton flavor equilibration, and we show how it reduces to a particularly simple form.